Efficient use of drumstick in multitier cropping system under semi-arid ecosystem (Indian Journal of Arid Horticulture, 2025)
To achieve the projected target of 220 MT of vegetable production by 2020, augmentation in vegetable production needs to be formulated for different cropping system to fully exploit the natural resources. Number of cropping systems have been developed for different ecosystems, however, a suitable vegetable based cropping system is lacking for semi-arid and arid ecosystem. Considering the nature of growth pattern of the component crops and their yield potential, drumstick (base crop) and cucurbits (climbers) have been chosen in the cropping system. An experiment comprising eleven treatments with three replications in randomized block design was conducted at Central Horticultural Experiment station, Vejalpur from 2004- 05 and 2005-06. The results revealed that the interaction of component crops did not significantly reduce the growth parameters of base crop (drumstick) over sole crop. Higher the cropping index (200%), drumstick equivalent yield (28.65 kg/ ha) and land equivalent ratio (2.39) has been observed in the treatment combining drumstick and ridge gourd. This multitier system reduced the cost of input by 70.1 and 64.0 per cent comparing bower system and local system respectively.
Keywords: Drumstick; cropping system; cucurbits